Konsep Kebijakan dan Implementasi Pendidikan Multikultural di Indonesia - Hasanuddin, Hikmah (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
A country known for its high level of pluralism is Indonesia. This can be likened to a double-edged sword, not only has the potential for progress, but also the potential for decline, this depends on the quality of its human resources. Of course, this shows how important multicultural education is in Indonesia. This research aims to explore the basic concepts of policy and implementation of multicultural education, as well as refreshing the urgency of multicultural education in Indonesia. The method used is literature study which involves collecting and analyzing information from written sources relevant to the research topic without conducting direct research. The research results identify the core principles of multicultural policy, implementation strategies, and their positive impact on inclusion and cross-cultural understanding in the educational environment. This research provides in-depth insight into the basic concepts of multicultural education policy and provides guidance for policy makers and educational practitioners to strengthen inclusion and diversity in educational institutions.